2016
DOI: 10.1038/nn.4370
|View full text |Cite|
|
Sign up to set email alerts
|

Selective synaptic remodeling of amygdalocortical connections associated with fear memory

Abstract: Neural circuits underlying auditory fear conditioning have been extensively studied. Here we identified a previously unexplored pathway from the lateral amygdala (LA) to the auditory cortex (ACx), and found that selective silencing of this pathway using chemo-and optogenetic approaches impairs fear memory retrieval. Dual-color in vivo two-photon imaging of mouse ACx showed pathwayspecific increases in the formation of LA axon boutons, dendritic spines of ACx layer-5 pyramidal cells, and putative LA-ACx synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
150
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 50 publications
15
150
2
Order By: Relevance
“…This result is consistent with a previous study showing that monocular deprivation increases spine formation and leads to higher spine density on the apical tufts of L5, but not L2/3, PNs in the binocular region of the mouse visual cortex (Hofer et al, 2009). A more recent work revealed pathway-specific increases in the formation of lateral amygdala axon boutons and dendritic spines of L5 PNs in the auditory cortex during fear conditioning, but no change in spine dynamics of L2/3 PNs (Yang et al, 2016). Given their high baseline spine dynamics, L2/3 PNs may have already reached the metabolic ceiling under baseline conditions, so cannot support higher spine dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with a previous study showing that monocular deprivation increases spine formation and leads to higher spine density on the apical tufts of L5, but not L2/3, PNs in the binocular region of the mouse visual cortex (Hofer et al, 2009). A more recent work revealed pathway-specific increases in the formation of lateral amygdala axon boutons and dendritic spines of L5 PNs in the auditory cortex during fear conditioning, but no change in spine dynamics of L2/3 PNs (Yang et al, 2016). Given their high baseline spine dynamics, L2/3 PNs may have already reached the metabolic ceiling under baseline conditions, so cannot support higher spine dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presynaptic partners of these spines remain elusive. Thus, a comprehensive understanding of the reorganization of synaptic circuits requires concurrent imaging of pre- and post-synaptic elements as illustrated by a recent study on the amygdalocortical circuit (Yang et al, 2016), or correlative light and electron microscopy (Knott et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the auditory cortex, whether primary or higher order, is essential for associating complex tones to emotional events (LeDoux, 2000; Letzkus et al, 2011; Yang et al, 2016). Conversely, the involvement of these cortices in the association of simple tones with US is more controversial (LeDoux, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yang et al . [101] imaged layer-5 pyramidal cell synapses and found that boutons tend to grow more often than spines after an auditory fear conditioning task.…”
Section: Functional Consequences Of Pre- and Postsynaptic Spike-timinmentioning
confidence: 99%